2020
DOI: 10.1364/prj.382535
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation using d33 in periodically poled lithium niobate microdisk resonators

Abstract: A fabrication process allowing for the production of periodically poled lithium niobate (PPLN) photonic devices with any domain pattern and unit size down to 200 nm is developed by combining semiconductor fabrication techniques and piezo-force-microscopy tips polarization. Based on this fabrication process, PPLN microdisk resonators with quality factors of 8 × 10 4 were fabricated from a Z-cut lithium niobate film. Second-harmonic generation (SHG) utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…With the assistance of chemomechanical polishing (CMP), the quality (Q) factors of LNOI microdisk cavities have been recently improved up to 10 7 [5,6], and the propagating loss of the LNOI waveguide has been reduced to as low as 0.027 dB/cm [7]. Using the nonlinearity of LN, various nonlinear optical effects, including sum frequency generation, second harmonic generation, difference frequency generation, and four-wave mixing, have been realized in LNOI microdisks, microrings, and waveguides [8][9][10][11][12][13][14][15][16][17]. Integrated LN electro-optic modulators with high operating frequencies and CMOS-compatible voltages have also been designed [18].…”
Section: Introductionmentioning
confidence: 99%
“…With the assistance of chemomechanical polishing (CMP), the quality (Q) factors of LNOI microdisk cavities have been recently improved up to 10 7 [5,6], and the propagating loss of the LNOI waveguide has been reduced to as low as 0.027 dB/cm [7]. Using the nonlinearity of LN, various nonlinear optical effects, including sum frequency generation, second harmonic generation, difference frequency generation, and four-wave mixing, have been realized in LNOI microdisks, microrings, and waveguides [8][9][10][11][12][13][14][15][16][17]. Integrated LN electro-optic modulators with high operating frequencies and CMOS-compatible voltages have also been designed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Poling of LNTF with a period of 747 nm was reported by optimized bipolar preconditioning [64], which may also apply to shorter period poling. And poled LNTF even with periods down to 200 nm has also been successfully demonstrated using the PFM method [29]. Backward QPM scheme is thus accessible in LNTF.…”
Section: Perspectives and Conclusionmentioning
confidence: 90%
“…Attracting approaches also involves electron beam writing, femtosecond laser direct writing, and atomic force microscope, which has been achieved at bulk surfaces [25][26][27][28] and is also applicable for LNTF. For example, Zhenzhong Hao et al have demonstrated domain engineering in LNTF microdisks by using piezoresponse force microscopy (PFM) [29].…”
Section: Shg With High Conversion Efficiencymentioning
confidence: 99%
“…With the energy conservation ω s = 2ω p , the perfect phase matching condition requires the refractive indexes of pump and signal laser to fulfil n(ω s ) = n(ω p ). To compensate the phase mismatching, techniques such as modal phase matching (MPM), [95,96] cyclic phase matching (CPM) [97,98] and quasi phase matching (QPM) [99][100][101][102] have been developed in LN thin film microresonators.…”
Section: Phase Matching Methodsmentioning
confidence: 99%